Analytical similarity assessment of MYL-1402O to reference Bevacizumab. (1st February 2022) - Goyal, Parag; Vats, Bhavesh; Subbarao, Malini; Honnappa, Chethan Gejjalagere; Kabadi, Pradeep; Rohil, Sheija; Bera, Arnab; Mehta, Gaurav R; Pai, Harish; Adhikari, Laxmi; Tagore, Ranitendranath; Sharma, Shulagna; et al.
ABSTRACT: Background: Bevacizumab (BEV) is a recombinant humanized monoclonal immunoglobulin G1 antibody that binds to vascular endothelial growth factor (VEGF)-A and acts as an antiangiogenic agent. It is approved for treatment of many cancer indications, including metastatic colorectal cancer and nonsquamous non–small cell lung cancer. Research Design and Methods: The analytical similarity of the BEV biosimilar MYL-1402O to reference BEV sourced from the European Union and United States was assessed using physicochemical and functional tests to support the clinical development of MYL-1402O. Assessment of physicochemical and analytical similarity showed that MYL-1402O has the same amino acid sequence and similar posttranslational modification profile as the reference BEV products. Results: The functional and biologic activity of MYL-1402O assessed using inhibition of VEGF-induced cell proliferation in human umbilical vein endothelial cells, inhibition of VEGF-induced VEGF receptor 2 phosphorylation, and fragment antigen and fragment crystallizable receptor binding, was comparable to reference BEV products. Conclusions: The totality of the data assessment confirms the high degree of similarity of MYL-1402O to reference BEV with respect to physicochemical and in vitro functional properties. The product quality data presented here, along with data from phase 1 clinical studies, demonstrate the similarity of MYL-1402O to reference BEV products, supporting further clinical development of this BEV biosimilar.